The impact of international conventions on family issues: The atypical family is a modal - الشيخ صالح بشير (مجلة الاجتهاد للدراسات القانونية والاقتصادية, 2023)
The international conventions on family issues aim to improve the conditions of individuals and society, to bring equality and development in various areas. The family is considered to be the most powerful natural social institution, achieving stability, social cohesion and the persistence of the human race. There is an urgent need to know the new concept linked with the atypical family formed by two persons of the same sex, also the nature of the term “alternative gender” for male and female and its impact on the presence and stability of the family. The study found an international decline in the normal family standing, recognition of various forms of family, the right to choose gender according to personal and psychological orientations, and endeavour to rearrange roles within the family, and the expansion of personal freedoms at the expense of the society’s basic unit, represented in the family which formed by husband, wife and their children.